Influence law and control mechanism of coal seam permeability on coal and gas outburst - Chaolin ZHANG; Mingliang LIU; Enyuan WANG; Peizhong WANG; Qiaozhen JIANG; Wei ZENG (Meitan xuebao)
Coal and gas outburst is a destructive gas dynamic disaster in coal mines, which seriously threatens the safety of coal mine production. Coal permeability is an important parameter that comprehensively reflects the characteristics of coal seams. The coal and gas outburst experiments under different permeability conditions (1.38×10−15、6.69×10−15、7.34×10−15和9.10×10−15 m2) were carried out using the self-developed multi-functional test system for coal and gas outburst simulation. The results show that with the increase of permeability of coal seam, the migration form of outburst two-phase flow gradually changes from bolting flow to stratified flow and dune flow, and the migration velocity and peak value of pulverized coal decrease gradually, from 31.98 m/s under 1.38×10−15 m2 condition to 20.10 m/s under 9.10×10−15 m2 condition. The shock wave generated by the outburst two-phase flow migration exhibits a phased evolution characteristic. The maximum absolute value of the valley value of shock wave overpressure in the negative phase pressure range is greater than the peak value of shock wave overpressure in the positive phase pressure range, and decreases at the front end of the roadway with the increase of coal seam permeability. The relative outburst strengths of four experiments are 75.63%, 44.65%, 38.01%, and 10.97%, respectively, and the fitting results show that the relative outburst strength decreases exponentially with the increase of coal seam permeability. According to the theoretical analysis, the gas pressure gradient acts on the coal in the form of seepage force, and the permeability of coal seam mainly affects the dynamic change of seepage force, and then affects the outburst strength of coal and gas outburst and the migration state of outburst two-phase flow. With the increase of coal seam permeability, the resistance to gas flow decreases, and the gas pressure decreases rapidly, making it difficult to form a high gas pressure gradient. At the same time, the seepage force near the exposed surface is low and quickly transfers to the distant location, unable to further damage the exposed coal seam, resulting in the decrease of outburst strength or even no outburst. Finally, from the perspectives of gas pressure gradient and gas seepage force, the evolution characteristics of the entire process of coal and gas outburst are systematically explored. It is found that coal seam permeability plays an important role in each stage of outburst. Combined with the current situation and difficulties in predicting outbursts in China, it is believed that coal seam permeability is expected to become a new indicator for predicting coal and gas outbursts. The key lies in determining the critical value based on the actual conditions of the coal mines, and the future prospects from experimental research, theoretical analysis, and engineering practice are proposed.